Prevalence and Forms of Workplace Bullying Among Health-care Professionals in Cyprus: Greek Version of "Leymann Inventory of Psychological Terror" Instrument - Theodora Zachariadou; Savvas Zannetos; Stella Elia Chira; Sofia Gregoriou; Andreas Pavlakis (Elsevier, 2018)
Background: Workplace bulling is a pervasive phenomenon with negative consequences for the health of victims and the productivity of organizations. The aim of this study was to measure the prevalence and forms of workplace bullying among employees working at the public health-care sector of Cyprus using the Greek version of Leymann Inventory of Psychological Terror (LIPT) instrument. Methods: A translation process was followed from the French to the Greek version of LIPT questionnaire. Test-retest reliability expressed by Pearson's correlation coefficient was 0.98 indicating excellent reproducibility. Internal consistency reliability assessed by Cronbach α coefficient was 0.87 suggesting high reliability. LIPT instrument was distributed among 403 employees working at the primary health-care setting and at the largest public hospital of Cyprus with response rate of 73.4%. Results: Women comprised the majority of participants (71.4%). Mean age was 43.3 years. Prevalence of workplace bulling according to Leymann's definition was 5.9%. Most common forms of bullying were "Being continuously interrupted" (17.2%) and "continuously being given new work assignments" (13.5%). Women were significantly more often exposed to at least one mobbing behavior than men within the previous year (49% vs. 35.7%, p = 0.038), whereas nurses were significantly exposed to at least one mobbing behavior as compared to physicians (53.3% vs. 31.4%, p = 0.004). Conclusion: This was the first study that examined the prevalence of workplace bullying in the public health-care sector by elaborating the Greek version of LIPT instrument. Results showed that workplace bullying is a common and complex phenomenon among health-care organizations. Keywords: Health-care professionals, Leymann Inventory of Psychological Terror questionnaire, Workplace bullying